2018
DOI: 10.14814/phy2.13676
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of inflammatory mediator expression in bovine endometrial cells: effects of lipopolysaccharide, interleukin 1 beta, and tumor necrosis factor alpha

Abstract: An abnormal uterine environment can influence maternal–fetal communication, conception rate and disrupt normal embryo development, thereby affecting fertility and the reproductive performance of dairy cows. Animal variability means that development of endometrial cell lines with appropriate characteristic are required. We evaluated the effect of an infectious agent (i.e., bacterial lipopolysaccharide; LPS) and proinflammatory mediators (i.e., Interleukin 1 beta; IL‐1β, and tumor necrosis factor alpha; TNFα) on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 72 publications
(125 reference statements)
1
24
0
Order By: Relevance
“…66 Likewise, the TNF-α 308 promoter polymorphism, which is associated with high TNF-α production, has been linked to increased implantation rates and a reduced rate of miscarriage. [77][78][79][80] However, this study is one of the first to evaluate the direct response of hESCs to bacterial endotoxin exposure during decidualization. 69,70 Moreover, recent studies have demonstrated that G-CSF treatment in women with recurrent IVF failure improved implantation and pregnancy rates.…”
Section: Identifying the Molecular Changes That Accompany Lps-inducmentioning
confidence: 99%
See 1 more Smart Citation
“…66 Likewise, the TNF-α 308 promoter polymorphism, which is associated with high TNF-α production, has been linked to increased implantation rates and a reduced rate of miscarriage. [77][78][79][80] However, this study is one of the first to evaluate the direct response of hESCs to bacterial endotoxin exposure during decidualization. 69,70 Moreover, recent studies have demonstrated that G-CSF treatment in women with recurrent IVF failure improved implantation and pregnancy rates.…”
Section: Identifying the Molecular Changes That Accompany Lps-inducmentioning
confidence: 99%
“…Induced cytokine expression in response to LPS has also been demonstrated in non-decidualized human, mouse, and bovine endometrial cells. [77][78][79][80] However, this study is one of the first to evaluate the direct response of hESCs to bacterial endotoxin exposure during decidualization. Interestingly, secreted levels of IL-12 and IFN-γ were significantly decreased in decidualized hESCs exposed to LPS compared to those that were not exposed to LPS.…”
Section: Characterizing Cytokine and Chemokine Release In Primary Hmentioning
confidence: 99%
“…9 A previous study of our group has shown the presence of transplanted ASCs on 3rd and 14th days after tendon transection, probably in response to the intense initial inflammatory process. B, Hydroxyproline concentration (mg/g tissue) of tendon RT: there was no significant difference between the experimental groups expression of Il1b, another proinflammatory cytokine, 40 it was observed a marked tendency to increase in the SC and L groups, corroborating with tendency to increase of Mmp8 gene expression in the same groups. No differences were observed in the expression of Tgfb1 among groups, but the higher concentration of IL-10 in the SC group corroborates the Our results do not demonstrate differences in the amount of TNF-α in the different groups, although the literature describes the anti-inflammatory role of LLL 38 and ASCs.…”
Section: Discussionmentioning
confidence: 65%
“…Significant differences between groups marked with the same letter (P < 0.05). B, Hydroxyproline concentration (mg/g tissue) of tendon RT: there was no significant difference between the experimental groups expression of Il1b, another proinflammatory cytokine, 40 it was observed a marked tendency to increase in the SC and L groups, corroborating with tendency to increase of Mmp8 gene expression in the same groups. Il1b has been identified as potent inducers of matrix metalloproteinases (MMPs).…”
Section: Discussionmentioning
confidence: 65%
“…The researchers evaluated the effects of the LPS and pro-inflammatory mediators (IL-1β and TNFα) on bovine endometrial epithelial (bEEL) and stromal (bCSC) cell lines by detecting gene expression and production of cytokine and eicosanoid biosynthesis pathway. Result showed bEEL and bCSC are brilliant models in vitro for intrauterine environment studies [17,18]. Other study used primary isolated endometrial epithelial and stromal cells and ex vivo organ culture (EVOCs) as well-characterized models of endometritis to explore cellular pathways that modulate inflammatory responses within the endometrial tissue.…”
mentioning
confidence: 99%